PENINGKATAN HASIL BELAJAR KOGNITIF BIOLOGI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THE POWER OF TWO PADA SISWA KELAS XI MADRASAH ALIYAH MADANI PAO-PAO KABUPATEN GOWA. - Herlina (Jurnal Biogenerasi, 2022)
This research is a classroom action research (Classroom Action Research) with the aim of improving students' cognitive learning outcomes through the application of the cooperative learning model The Power of Two students of class XI.b Madrasah Aliyah Madani Pao-pao, Gowa Regency on excretory system material. The research subjects consisted of 40 students with the implementation stage carried out in two cycles (Cycle I and Cycle II), while the data obtained were analyzed using quantitative descriptive analysis. The results showed that the application of the cooperative learning model type The Power of Two can improve cognitive learning outcomes for students of class XI.b Madrasah Aliyah Madani Pao-pao, Gowa Regency. The increase is shown from the results of the research cycle I to cycle II, namely the average value of students' cognitive learning outcomes increased from 59.00 to 68.80 and an increase in the percentage of students who completed from 45.00% to 87.5%. Based on the results of quantitative analysis, the increase in students' cognitive biology learning outcomes from cycle I to cycle II was 42.5%, so it can be concluded that there was an increase in cognitive learning outcomes for students in class XI.b Madrasah Aliyah Madani Pao-pao, Gowa Regency.